Observed direction of the guard dogs’ (N = 15) behaviour when guarding horses. - Konstanze Krueger (6750239) (2025)
In direct field observation, the guard dogs’ behaviour varied according to whether it was directed at their own species or others (Wilcoxon signed rank tests: N = 15, V = 71, p = 0.01), and they showed all behaviour categories towards the guarded horses. Guard dogs displayed mostly neutral and friendly and, in one case, dominant behaviour towards their own species, they showed mostly anxious and neutral, but also friendly and dominant behaviour towards the guarded species, and they were mostly dominant, but also anxious, neutral, and sometimes friendly, towards others. The category “others” included external persons, dogs, cats, deer, birds, bikers, and cars.